The use of invisible aligners by dentists in the city of Manaus/Amazonas (Research, Society and Development, 2023)
Introduction: The orthodontic procedure with invisible aligners has gained important notoriety in current times, especially among patients seeking effective treatment combined with the oral cavity. Given the constant search for more discreet or “invisible” orthodontics, the development of devices that meet these expectations has become increasingly frequent. Objective: aims to identify dental surgeons, orthodontists and general practitioners who use invisible aligners and the acceptance of this orthodontic treatment alternative by professionals, as well as by patients in the city of Manaus/AM. Methodology: This is a statistical, quantitative and cross-sectional study, developed with dental surgeons and orthodontists in the city of Manaus/ AM., using data collected through a questionnaire. The results highlight the advantages of therapy with clear aligners, such as pleasant aesthetics, better oral hygiene, ease of removal, comfort and their applicability in a variety of cases, in addition to discreet attachments and specific benefits for certain tooth movements. Final considerations: Therefore, obtaining representative statistical data on their application is extremely relevant, providing a solid scientific basis for understanding the reality of the use of these devices in the region.